Epidemiological approach to nematode polyparasitism occurring in a sympatric wild ruminant multi-host scenario. (7th June 2021) - Carrau, Tessa; Martínez-Carrasco, Carlos; Garijo, María Magdalena; Alonso, Francisco; Vizcaíno, Luis León; Herrera-Russert, José; Tizzani, Paolo; Ruiz de Ybáñez, Rocío
Abstract: The epidemiology behind multi-host/multi-parasite systems is particularly interesting to investigate for a better understanding of the complex dynamics naturally occurring in wildlife populations. We aimed to approach the naturally occurring polyparasitism of gastrointestinal nematodes in a sympatric wild ruminant scenario present in south-east Spain. To this end, the gastrointestinal tract of 252 wild ruminants of four different species (red deer, Cervus elaphus ; mouflon, Ovis aries musimon ; Iberian ibex, Capra pyrenaica and fallow deer, Dama dama ) were studied in Cazorla, Segura y Las Villas Natural Park (Andalusia, Spain). Of the analysed animals, 81.52% were positive for parasite infection and a total of 29 nematode species were identified. Out of these, 25 species were detected in at least two host species and 11 parasitized all ruminant species surveyed. The multi-host interaction between these nematodes and the four host species is discussed under the perspective of host family-based differences.